2003
DOI: 10.1080/02724980244000639
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Subsystems for the Parafoveal Processing of Spatial and Linguistic Information during Eye Fixations in Reading

Abstract: Two experiments examined readers' use of parafoveally obtained word length information for word recognition. Both experiments manipulated the length (number of constituent characters) of a parafoveally previewed target word so that it was either accurately or inaccurately specified. In Experiment 1, previews also either revealed or denied useful orthographic information. In Experiment 2, parafoveal targets were either high-or low-frequency words. Eye movement contingent display changes were used to show the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
69
4
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 44 publications
5
69
4
6
Order By: Relevance
“…On the basis of our findings and those of Inhoff et al (2003), it seems to us that the most likely interpretation within the frame of the EOVP model is that word length information and linguistic information independently influence the skipping decision. Word length is used in the very beginning of the fixation to obtain a rough estimate of the chances of recognising the parafoveal word by the end of the fixation, and this estimate is used to decide whether or not to programme a saccade to this word.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…On the basis of our findings and those of Inhoff et al (2003), it seems to us that the most likely interpretation within the frame of the EOVP model is that word length information and linguistic information independently influence the skipping decision. Word length is used in the very beginning of the fixation to obtain a rough estimate of the chances of recognising the parafoveal word by the end of the fixation, and this estimate is used to decide whether or not to programme a saccade to this word.…”
Section: Discussionmentioning
confidence: 78%
“…However, other recent evidence reported by Inhoff et al (2003) tempers the enthusiasm about this possibility. Inhoff et al manipulated the length information of parafoveal target words by either presenting the correct word or by replacing one middle letter of the word with a blank space so that it seemed as if there were two short words coming up in the parafovea (e.g., subject vs. sub ect).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous research has demonstrated that word length and word boundary information is used by the eye movement targeting system during reading Rayner, Fischer, & Pollatsek, 1998). Furthermore, studies have demonstrated that presenting inaccurate word length information or removing spaces between words in the parafovea leads to disruptions in normal reading behavior (Inhoff, Radach, Eiter, & Juhasz, 2003;Inhoff, Starr, Liu, & Wang, 1998;Juhasz, White, Liversedge, & Rayner, 2008;Morris, Rayner, & Pollatsek, 1990;Rayner et al, 1998;Spragins, Lefton, & Fisher, 1976). Prior research has also demonstrated that word length positively correlates with the number of fixations received during normal reading, leading to more fixations on long than on short words (Rayner & McConkie, 1976;Rayner, Sereno, & Raney, 1996).…”
mentioning
confidence: 91%
“…Previous studies have defined, operationalized, and manipulated orthographic familiarity, informativeness, legality, saliency, and regularity in a variety of ways in an attempt to highlight the possible role of orthographic characteristics as important driving factors behind the observed differences in initial fixation landing positions (Everatt & Underwood, 1992;Hyönä et al, 1989;Inhoff et al, 2003;Radach et al, 2004;Underwood et al, 1990;White, 2008;White & Liversedge 2004, 2006b). Across many experiments, areas of text containing difficult-toprocess or visually "salient" low-level linguistic information seem to be strongly correlated with deviations from predicted spatial saccade characteristics (i.e., deviation from the PVL).…”
mentioning
confidence: 99%